Tropical aesthetics of black modernism - Noel, Samantha A. (Duke University Press, 2021)
In Tropical Aesthetics of Black Modernism, Samantha A. Noël investigates how Black Caribbean and American artists of the early twentieth century responded to and challenged colonial and other white-dominant regimes through tropicalist representation. With depictions of tropical scenery and landscapes situated throughout the African diaspora, performances staged in tropical settings.
English
Keywords: N5300-7418 Visual Arts- History; Central America